Let's solve the equation step by step, filling in the missing terms and descriptions:
-
Start with the equation:
\(3(9w - 1) = 10w - 3\) -
Apply the distributive property:
\(3 \cdot 9w - 3 \cdot 1 = 10w - 3\)
This simplifies to:
\(27w - 3 = 10w - 3\) -
Add 3 to both sides:
\(27w - 3 + 3 = 10w - 3 + 3\)
This simplifies to:
\(27w = 10w\) -
Subtract \(10w\) from both sides:
\(27w - 10w = 10w - 10w\)
This simplifies to:
\(17w = 0\) -
Now, divide both sides by 17:
\(\frac{17w}{17} = \frac{0}{17}\)
This simplifies to:
\(w = 0\)
Now, summarizing the steps with the correct terms and descriptions:
- Apply the distributive property: \(3(9w - 1)\) becomes \(27w - 3\)
- Add 3 to both sides: \(27w - 3 + 3 = 10w - 3 + 3\)
- Subtract \(10w\) from both sides: \(27w - 10w = 10w - 10w\)
- Divide both sides by 17: \(w = 0\)
Thus, the solution to the equation is \(w = 0\).